The Voices of Black South African Men on Renal Dialysis at a Tertiary Hospital: A Phenomenological Inquiry. Issue 5 (September 2021) - Mokwena, Jabu; Sodi, Tholene; Makgahlela, Mpsanyana; Nkoana, Shai
The study explored the psychosocial experiences of rural black South African men undergoing renal dialysis in a tertiary hospital. Twenty men aged between 20 and 59 years ( Meanage = 40.65 yrs; SD = 12.52) participated in the study. Participants were recruited purposefully. Data were collected over a period of 4 months through in-depth face-to-face interviews and analyzed using the Interpretative Phenomenological Analytical method. The following three key themes were extracted from the interviews: (a) the emotional pain and fear of death following a diagnosis of ESRD; (b) living on dialysis interferes with the management and handling of "manly" responsibilities and duties and, (c) dialysis as a challenging yet life-saving measure. The findings further suggest that renal dialysis has an impact on men's sense of masculinity and has the potential to complicate the management of renal failure. The paper concludes by recommending that cultural and community factors be taken into account when considering interventions to manage the health of men living with renal conditions.